APLIKASI SHARING PRINTER MELALUI VIRTUAL PRIVATE NETWORK (VPN) SEBAGAI MEDIA PENGIRIMAN DOKUMEN - Muhsyi, Abdul; Affandi, Luqman (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2018)
Telephone technology required for a means of communication between the company,employees and customers. Not only communication course, telephone technology can also submit adocument be printed through fax machine technology that is connected to the network telephone.However telepone technology users have decreased. Because consumers prefer mobile phone orInternet services as a means of communication and cause deterioration in telephone users. So thetechnology is connected in a network telephone also affected, such as fax machines. Internetservice can not submit documents such as mold, as well as a fax machine. These services may beneeded. To send a document without a fax machine, can be done using a printer sharingapplication that allows users to send documents via the VPN. Delivery of documents to the printerthrough a VPN can be done without the use fax machines. Require a small fee to send documentsvia the VPN. Transmission speed per document is superior. The quality of the resulting documentsprinter depending on the printer settings when printing document. VPN security systems can be setalone.Keywords: Facsimile, Printer, Document, VPN, Server, Client.Â